Understanding practitioner perspectives of youth healthcare using thematic and lexical analyses - Ann Dadich; Carmen Jarrett (Wiley, 2019)
Abstract Background Youth health issues represent a "wicked problem" - they are complex and multifaceted. Furthermore, they are likely to require novel approaches to understand their complexity and develop novel solutions. Objective Given the importance of youth healthcare, and the need for novel approaches, the aim of this article was to demonstrate the innovative use of two research methods - thematic and lexical analyses - to better understand practitioner perspectives of youth healthcare. It clarifies the factors that shape practitioner ability to support young people and opportunities to improve practice. Design and Setting Focus groups and interviews were conducted with 37 youth health practitioners. They represented government and non‐government services; hospital and community services; and metropolitan and regional services. Results Thematic analysis highlighted the complexity of participants' work and the judgements made as they negotiated relationships with young people and ancillary services. Lexical analysis revealed two hitherto neglected dimensions of the complexity of youth healthcare - uncertainty and corporeality. Discussion In addition to affirming the complexities of youth healthcare, this study revealed how practitioners (can) negotiate these complexities. These findings were only possible because of the innovative use of the two research methods. Conclusions This study has important theoretical, methodological and practical implications. Theoretically, it is the first to view the complexities of youth healthcare through the wicked problem lens. Methodologically, it highlights the complementary value of thematic and lexical analyses. Practically, it reinforces the importance of policy support and professional development to enable practitioners to grasp the complexities of their work.